The legal status of drinking water sources in indigenous communities in the Americas. Human rights or assets that can be expropriated, exploited, and commercialized? - Cruz Ángeles, Jonatán (REVISTA ELECTRONICA IBEROAMERICANA, 2022)
In the Inter-American system, we could notice how the lack of access to drinking water affects people and communities, historically discriminated against, including indigenous, native, or tribal communities. Access to drinking water is closely related to respect and guarantee of several human rights such as the right to life, bodily autonomy, and local people’s health. Therefore, this paper reviews if we should consider the legal status of drinking water sources located in lands that traditionally belonged to indigenous communities as individual or community human rights or as assets that can be expropriated, exploited, and commercialized by public institutions or private companies.
Keywords: indigenous peoples; Americas; drinking water; water resources; appropriation; exploitation; commercialization